FEMINISM THOUGHTS IN ALICE MUNRO’S SELECTED SHORT STORIES - Abu Fanani; Ima Masofa; Irwan Sumarsono; Ahmad Syaikhu; Mahfud Muhamad Sodiq (JEELL (Journal of English Education, Linguistics and Literature) English Departement of STKIP PGRI Jombang, 2023)
This study analyzes Alice Munro’s feminism thoughts in her selected short stories; Alice Munro, whose family has undergone oppression especially her mother and her herself since she was in her childhood, expresses the right of ‘speaking’ through the female characters about equal rights of women she saw as well as she experienced since her childhood, the women who are oppressed by man as well as the cultural gaps. Using Feminism as the method and sociology of literature as the theory, I find that Alice Munro’s feminism’s thoughts are reflected through the female characters who are against men and culture domination in the selected short stories.